2018
DOI: 10.1364/osac.1.000274
|View full text |Cite
|
Sign up to set email alerts
|

Fully self-referenced frequency comb consuming 5 watts of electrical power

Abstract: We present a hybrid fiber/waveguide design for a 100-MHz frequency comb that is fully self-referenced and temperature controlled with less than 5 W of electrical power. Selfreferencing is achieved by supercontinuum generation in a silicon nitride waveguide, which requires much lower pulse energies (~200 pJ) than with highly nonlinear fiber. These lowenergy pulses are achieved with an erbium fiber oscillator/amplifier pumped by two 250-mW passively-cooled pump diodes that consume less than 5 W of electrical pow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The rms of the noise is < 0.42 mHz demonstrating the excellent relative stability of the repetition frequency in long term operation. We did not use the metal-coated fiber in the f rep lock, however, it might be successfully used for simple and low-power thermal stabilization of a mode-locked oscillator, as shown in [7].…”
Section: Laser Setup and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rms of the noise is < 0.42 mHz demonstrating the excellent relative stability of the repetition frequency in long term operation. We did not use the metal-coated fiber in the f rep lock, however, it might be successfully used for simple and low-power thermal stabilization of a mode-locked oscillator, as shown in [7].…”
Section: Laser Setup and Characteristicsmentioning
confidence: 99%
“…Operation outside the laboratory requires compact, low-cost and low power consumption comb sources, which are enabled by the use of fiber-based technology [5,6]. Recently a fully self-referenced frequency comb based on an Er-doped fiber laser was reported, with electrical power consumption of only 5 W [7]. It has been also proven that fiber-based frequency combs are ready for space travel and resistant to microgravity conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a silicon nitride (SiN x ) platform is compatible with silicon technology and offers a nonlinear index 10 times higher than that of silicon dioxide with negligible TPA in the near-infrared wavelength range [16]. Hence, in the last decade, multiple studies have demonstrated wide SCG in SiN x waveguides featuring broadband spectra [17][18][19][20][21][22][23][24][25][26][27][28][29]. Applications of supercontinuum in SiN x have been shown with, for example, an f -to-2f interferometer for carrier envelope offset frequency detection [21,24,[30][31][32], or mid-infrared generation of dispersive waves (DWs) for gas spectroscopy [28].…”
Section: Introductionmentioning
confidence: 99%
“…The latter fiber lasers, built with off-the-shelf all-fiber components, allowed for even more compact, energy efficient and robust systems. Subsequently these Er:fiber OFCs have seen the most commercial success and are the most commonly used OFCs system to date 15,[38][39][40][41][42] . Other notable fiber lasers include the high power 1 μm Yb:fiber 43 , which when combined with high power Ytterbium amplifiers are ideal candidates for high-harmonic generation in the XUV for direct comb spectroscopy 44 , as well as the realization of 2 μm Thulium doped fiber-OFCs 45 .…”
Section: What Is An Ofc and How Does It Workmentioning
confidence: 99%
“…OFCs quickly found application to a multitude of diverse optical, atomic, molecular, and solid-state systems, including X-ray and attosecond pulse generation 4 , coherent control in field-dependent processes 5,6 , molecular fingerprinting 7 , trace gas sensing in the oil and gas industry 8 , tests of fundamental physics with atomic clocks 9 , calibration of atomic spectrographs 10 , precision time/frequency transfer over fiber and free-space 11 , arbitrary waveform measurements for optical communication 12 , and precision ranging 13 . To support this broad application space, OFCs have seen rapid changes in laser development to enable coverage at different spectral regions, varying frequency resolutions, and to enable the development of systems that offer lower size, weight and power (SWAP) [14][15][16][17] .…”
mentioning
confidence: 99%